The serum high-sensitive C reactive protein and homocysteine levels to evaluate the prognosis of acute ischemic stroke - Yoldas, Tahir; Gonen, Murat; Godekmerdan, Ahmet; Ilhan, Fulya; Bayram, Ednan (Hindawi Ltd, 2007)
Ischemic stroke is one of the most common causes of death worldwide and is most often caused by thrombotic processes. We investigated the changes in hsCRP and homocysteine levels, two of these risk factors, during the acute period of ischemic stroke and evaluated the relationship between these levels and the short-term prognosis. HsCRP and homocysteine levels were measured at the 2nd, 5th, and 10th days in forty patients admitted within second of an ischemic stroke. The clinical status of the patients was simultaneously evaluated with the Scandinavian stroke scale. The results were compared with 40 healthy control subjects whose age and sex were matched with the patients. The mean hsCRP levels of the patients were 9.4 +/- 7.0mg/L on the 2nd day, 11.0 +/- 7.4mg/L on the 5th day, and 9.2 +/- 7.0mg/L on the 10th day. The mean hsCRP level of the control subjects was 1.7 +/- 2.9mg/L. The mean hsCRP levels of the patients on the 2nd, 5th, and 10th days were significantly higher than the control subjects (P <.001). The patients' mean homocysteine levels were 40.6 +/- 9.6 mol/L on the 2nd day, 21.7 +/- 11.1 mol/L on the 5th day, and 20.7 +/- 9.2 mol/L on the 10th day. The mean homocysteine level of the control subjects was 11.2 +/- 1.1 mol/L. The homocysteine levels of the patients were higher than the control subjects at all times (P <.01). In conclusion, patients with stroke have a higher circulating serum hsCRP and homocysteine levels. Short-term unfavorable prognosis seems to be associated with elevated serum hsCRP levels in patients with stroke. Although serum homocysteine was found to be higher, homocysteine seems not related to prognosis.
Keywords: Plasma Homocysteine; Cardiovascular Risk; Disease; Hyperhomocysteinemia; Homocyst(E)Ine; Interleukin-6; Inflammation; Association; Markers